Perinatal Outcomes After Emergency Cervical Cerclage for Cervical Insufficiency with Prolapsed Membranes - Pang, Qi (Med Sci Monit, 2019)
BACKGROUND: To study the clinical effective of emergency cervical cerclage (ECC) in pregnant women who have cervical insufficiency with prolapsed membranes. MATERIAL/METHODS: This study was devised as a retrospective cohort in a single medical center, in which we collected clinical data from patient records. Inclusion criteria were: physical examination indicated ECC was performed at 15 to 25 gestational weeks at the Sixth Medical Center of the PLA General Hospital, and singleton pregnancy. The collected clinical data included: duration of pregnancy at delivery, interval between ECC and delivery, neonatal weight, neonatal mortality, neonatal morbidity, and Neonatal Intensive Care Unit (NICU) admission. RESULTS: We included 50 women with singleton pregnancies. No surgical complications occurred in any patients. The gestational age at cerclage was 21.3±2.2 weeks. No patients had membrane damage due to surgery. No surgical complications were reported. Five (10%) patients underwent chorioamnionitis. The time interval between ECC and delivery was 11.2±7.1 weeks. The mean gestational age at delivery was 34.1 weeks. The rate of vaginal delivery was 96%. Ten patients had pregnancy lasting longer than 36 weeks. The mean neonate delivery weight was 2510.7 g. Twenty neonates were admitted to the Neonatal Intensive Care Unit (NICU), and the mean NICU stay was 21 days. CONCLUSIONS: ECC has good perinatal results. Our results provide clinical evidence for the efficacy and risks of ECC.